Occurrence, in the city of São Paulo, of a lysine-decarboxylase negative biotype of Salmonella typhimurium - Pessôa, Gil Vital Alvares (1978)
Lysine was not decarboxilated by 8.9% of the strains of Salmonellatyphimurium which were isolated from human sources during 13 moriths(starting in august, 1976). It is suggested that Iysirie decarboxylase nega tive strains of S. typhimurium may be related to hospital infections.